2014
DOI: 10.4103/0976-237x.137925
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of salivary glucose, blood glucose and oral candidal carriage in the saliva of type 2 diabetics: A case-control study

Abstract: Objectives:To study the correlation between blood glucose levels and salivary glucose levels in type 2 diabetic patients, to study the relationship between salivary glucose levels and oral candidal carriage in type 2 diabetic patients and to determine whether salivary glucose levels could be used as a noninvasive tool for the measurement of glycemic control in type 2 diabetics.Study Design:The study population consisted of three groups: Group 1 consisted of 30 controlled diabetics and Group 2 consisted of 30 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 13 publications
6
63
0
7
Order By: Relevance
“…The glucose levels of both blood and saliva are in agreement, with higher values in the uncontrolled diabetic group, followed by the group with diabetic and healthy individuals. This is consistent with the results obtained in earlier reports, wherein compared with control, the glucose levels were significantly higher in saliva samples of controlled and uncontrolled diabetics 23 . The main reason behind the presence of glucose in the saliva is due to its diffusion through semipermeable membrane 15 .…”
Section: Resultssupporting
confidence: 93%
“…The glucose levels of both blood and saliva are in agreement, with higher values in the uncontrolled diabetic group, followed by the group with diabetic and healthy individuals. This is consistent with the results obtained in earlier reports, wherein compared with control, the glucose levels were significantly higher in saliva samples of controlled and uncontrolled diabetics 23 . The main reason behind the presence of glucose in the saliva is due to its diffusion through semipermeable membrane 15 .…”
Section: Resultssupporting
confidence: 93%
“…3d, inset). [35][36][37][38] To evaluate the ability of the sensor to detect glucose in saliva, we collected a saliva sample from a healthy, non-diabetic volunteer who was asked to fast 12 h before the extraction of saliva. Using a commercially available glucose assay kit, we found glucose in this sample at a concentration of 28 µM.…”
Section: Resultsmentioning
confidence: 99%
“…4b). [35][36][37][38] Diabetic patients are advised to keep their blood glucose levels close to the target range below 7 mM (fasting). 39,40 Recent studies have demonstrated a significant positive correlation between the concentration of glucose in saliva and blood for healthy and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Of the 19 studies, 16 revealed a positive correlation between SG levels and BG/serum glucose levels. It is worth pointing out that SG values measured by groups from India, Iran, and Brazil 23-29 vary a lot from the others.…”
Section: Original Articlementioning
confidence: 99%